IgM Repertoire Biodiversity is Reduced in HIV-1 Infection and Systemic Lupus Erythematosus - Yin, Li; Hou, Wei; Liu, Li; Cai, Yunpeng; Wallet, Mark A.; Gardner, Brent P.; Chang, Kaifen; Lowe, Amanda C.; Rodriguez, Carina A.; Sriaroon, Panida; Farmerie, William G.; Sleasman, John W.; et al. (Frontiers in Immunology, 2013)
Background: HIV-1 infection or systemic lupus erythematosus [SLE] disrupt B cell homeostasis, reduce memory B cells, and impair function of IgG and IgM antibodies. Objective: To determine how disturbances in B cell populations producing polyclonal antibodies relate to the IgM repertoire, the IgM transcriptome in health and disease was explored at the complementarity determining region 3 [CDRH3] sequence population level. Methods: 454-deep pyrosequencing in combination with a novel analysis pipeline was applied to define populations of IGHM CDRH3 sequences based on absence or presence of somatic hypermutations [SHM] in peripheral blood B cells. Results: HIV or SLE subjects have reduced biodiversity within their IGHM transcriptome compared to healthy subjects, mainly due to a significant decrease in the number of unique combinations of alleles, although recombination machinery was intact. While major differences between sequences without or with SHM occurred among all groups, IGHD and IGHJ allele use, CDRH3 length distribution, or generation of SHM were similar among study cohorts. Antiretroviral therapy failed to normalize IGHM biodiversity in HIV-infected individuals. All subjects had a low frequency of allelic combinations within the IGHM repertoire similar to known broadly-neutralizing HIV-1 antibodies. Conclusions: Polyclonal expansion would decrease overall IgM biodiversity independent of other mechanisms for development of the B cell repertoire. Applying deep sequencing as a strategy to follow development of the IgM repertoire in health and disease provides a novel molecular assessment of multiple points along the B cell differentiation pathway that is highly sensitive for detecting perturbations within the repertoire at the population level.